ANALISIS PERAN MODAL SOSIAL TERHADAP KEBERHASILAN PEMELIHARAAN SAPI PERAH DI DESA SUMOGAWE KECAMATAN GETASAN KABUPATEN SEMARANG - Dwi Putri Puspitasari; Lasmono Tri Sunaryanto (Fakultas Pertanian, Universitas Janabadra, 2023)
The success of livestock farming is always associated with economic capital as indicated by the amount of income and capital. There is a main capital in the success of breeding, namely social capital. The research objective was to find out what role social capital plays in the successful maintenance of dairy farmers in Sumogawe Village, Getasan District, Semarang Regency. The research was conducted in January - February 2022 in Sumogawe, Getasan District, Semarang Regency. This type of research is qualitative. Data collection techniques with interviews. The variable in this study is social capital which consists of trust norms and networks. Participants in this study consisted of group leaders, administrators and members. The analysis technique uses descriptive qualitative. The results showed that social capital has an important role in the successful maintenance of dairy farmers in Sumogawe Village, Getasan District, Semarang Regency, namely by giving each member's trust to the head of KUD and vice versa. Salin provides information regarding the capital network and maintaining norms among members of dairy farmers. Trust begins with the election of management by members, active management in carrying out activities and active management in developing networks so that the business is a dairy cow. The network is in the form of loan capital in the form of People's Business Credit (KUR) and establishes cooperation with the government in the form of training. Norma with milk price agreement. Keywords: social capital, dairy cows, norm, network, trust. INTISARIKeberhasilan usaha tenak selalu dikaitkan dengan modal ekonomi yang ditunjukkan dengan besarnya pendapatan dan modal. Terdapat modal utama dalam keberhasilan beternak yaitu modal sosial. Tujuan penelitian untuk mengetahui apa peran modal sosial dalam keberhasilan pemeliharaan peternak sapi perah di Desa Sumogawe, Kecamatan Getasan Kabupaten Semarang. Penelitian dilakukan pada bulan januari – Febuari 2022 di Sumogawe Kecamatan Getasan Kabupaten Semarang. Jenis penelitian ini adalah kualitatif. Teknik pengambilan data dengan wawancara. Variabel pada penelitian ini adalah modal sosial yang terdiri dari Trust (kepercayaan) norm (norma) dan network (jaringan). Partisipan pada penelitian ini terdiri dari ketua kelompok, pengurus dan anggota. Teknik analisis menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Modal sosial memiliki peran penting dalam keberhasilan pemeliharaan peternak sapi perah di Desa Sumogawe, Kecamatan Getasan Kabupaten Semarang, yaitu dengan saling memberikan kepercayaan anggota ke ketua KUD dan sebaliknya. Saling memberikan informasi mengenai jaringan permodalan dan menjaga norma antar anggota peternak sapi perah. Kepercayaan berawal dari pemilihan pengurus oleh anggota, keaktifan pengurus dalam melakukan kegiatan serta pengurus aktif dalam melakukan pengembangan jaringan sehingga usaha sapi perah. Jaringan berupa modal pinjaman berupa Kredit Usaha Rakyat (KUR) serta menjalin kerjasama dengan pemerintah berupa pelatihan. Norma dengan kesepakatan harga susu.. Kata kunci: Modal sosial, sapi perah, norma, kepercayaan, jejaring.